2020
DOI: 10.1021/acs.joc.0c02630
|View full text |Cite
|
Sign up to set email alerts
|

Selenocyanation of Aryl and Styryl Methyl Ketones in the Presence of Selenium Dioxide and Malononitrile: An Approach for the Synthesis of α-Carbonyl Selenocyanates

Abstract: Single-crystal XRD data of 3a and copies of 1 H and 13 C NMR of all synthesized compounds (PDF)Accession Codes CCDC 2041476 contains the supplementary crystallographic data for this paper. These data can be obtained free of charge via www.ccdc.cam.ac.uk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…[43] In 2020, Marpna and coworkers also established a similar approach for the selenocyanation of aromatic ketones (118/ 119) using the combination of SeO 2 with CH 2 (CN) 2 as the SeCN initiator. [44] The technique was performed with aryl methyl ketones (118 a-118 i) efficiently under optimized condition, endured by miscellaneous considerable substituents (e. g., 4-Me, 2-OMe, 4-F, 3-Cl, 2-Br, 3-NO 2 , 2,4-dimethoxy, 2,4,6-trimethyl), and usually delivered the intended α-carbonyl selenocyanates (120 a-120 i) in moderate to good yields (Scheme 61a). The procedure was moreover acceptable to further heteroaryl methyl ketones compounds such as 1-(furan-2-yl)propan-1-one (118 j) and 1-(thiophen-2-yl)propan-1-one (118 k).…”
Section: Dicyanogen Triselenide (Se(secn) 2 ) Used As An Alternative ...mentioning
confidence: 99%
See 2 more Smart Citations
“…[43] In 2020, Marpna and coworkers also established a similar approach for the selenocyanation of aromatic ketones (118/ 119) using the combination of SeO 2 with CH 2 (CN) 2 as the SeCN initiator. [44] The technique was performed with aryl methyl ketones (118 a-118 i) efficiently under optimized condition, endured by miscellaneous considerable substituents (e. g., 4-Me, 2-OMe, 4-F, 3-Cl, 2-Br, 3-NO 2 , 2,4-dimethoxy, 2,4,6-trimethyl), and usually delivered the intended α-carbonyl selenocyanates (120 a-120 i) in moderate to good yields (Scheme 61a). The procedure was moreover acceptable to further heteroaryl methyl ketones compounds such as 1-(furan-2-yl)propan-1-one (118 j) and 1-(thiophen-2-yl)propan-1-one (118 k).…”
Section: Dicyanogen Triselenide (Se(secn) 2 ) Used As An Alternative ...mentioning
confidence: 99%
“…[44] The reaction began with the enolization of ketone (118), which was accompanied by a nucleophilic attack of enolate ketone (118 A) on the electrophilic selenium atom of TSD, a selenocyanating reagent prepared by the reaction of SeO 2 with CH 2 (CN) 2 , resulting in the creation of αcarbonyl selenocyanates 120 (Scheme 62). [44]…”
Section: Dicyanogen Triselenide (Se(secn) 2 ) Used As An Alternative ...mentioning
confidence: 99%
See 1 more Smart Citation
“…They also find applications as electrocatalysts 2 . Literature data reported thousands of articles about many technological applications that benefits from selenium dioxide as selenating agent under simple reacting conditions 3 . However, articles which consider SeO 2 as a solid compound suitable for electronic applications are almost absent.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the course of the SeO 2 -mediated reaction is dictated by the nature of the acid as well as the solvent used in a particular set of reactions. Thus, as part of our ongoing research on the synthetic utility of selenium dioxide in organic synthesis, ,, we wish to report here a direct and efficient one-step protocol for the synthesis of oxygen-based fused heterocyclic compounds (3a-aryldihydro-[1,3]­dioxolo­[4,5- d ]­[1,3]­dioxole-2,5-diyl)­bis­(phenylmethanones) by self-condensation of arylglyoxals derived from arylketones in the presence of SeO 2 and trifluoroacetic acid (TFA) (Scheme b).…”
Section: Introductionmentioning
confidence: 99%